Hazard Identification, Risk Assessment and Control (HIRAC) of Fablab Setting and Infrastructure at President University - Manik, Yosef Barita Sar; Manurung, Gracia Natalie Emmanuela; Kimberly, Jaqueline Andrea; Rahayu, Wanti; Haidar, Muhammad Labib (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2026)
This study demonstrates the methodological contribution of applying the Hazard Identification, Risk Assessment, and Control (HIRAC) framework to a previously underexplored setting: an academic Fabrication Laboratory (FabLab). Key findings reveal that the facility’s pre-assessment safety profile was medium-high, primarily due to critical hazards such as exposed electrical cables and obstructed emergency equipment. By employing a systematic, qualitative approach and implementing a tailored control plan based on the hierarchy of controls, the study successfully reduced the overall risk level to low-medium. The research concludes that the HIRAC method offers a replicable and effective model for proactive risk management in academic makerspaces, ultimately enhancing safety culture through structured assessment and prioritized intervention.